Digital rights management (DRM) in libraries of public universities in Jordan. Issue 8 (11th November 2019) - Abu Sirhan, Afaf; Abdrabbo, Khalid Mohamad; Ahmed Ali Al Tawalbeh, Serhan; Hamdi Ahmed, Mustafa; Ali Helalat, Mohammad
Abstract : Purpose: The purpose of this paper is to illustrate some methods to protect digital libraries using digital rights management (DRM) technologies and specifically the methods applied at the digital libraries of Jordan universities. Design/methodology/approach: A descriptive research method has been used to examine the extent of DRM in digital libraries of universities in Jordan. Findings: Majority of the universities in Jordan use different methods of protection including coding, identification, authenticity and digital watermark. However, methods including digital signature, digital fingerprint, copy detection systems and pay system have not been employed within Jordanian universities. The use of copyright management systems has been limited, which shows the weakness in the use of technological protection within the investigated libraries. Originality/value: This study has shown contribution to the development of digital libraries that are based on the protection of new technology and are able to provide better services to users without concern about protecting publishers' rights.